PERAN MEDIA KOMUNIKASI DAN EFEKNYA BAGI PENGEMBANGAN DESA WISATA DI BALI - Ida Bagus Putu Supriadi; Ida Ayu Kartika Maharani (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2021)
This study aims to identify and interpret data about the role of communication media, and their effects on the development of tourist villages in Bali. This research is included in the category of qualitative research, which uses a phenomenological approach to communication. Data and information about alternative models of Balinese cultural tourism development, processed based on the perspective of dependency theory, are used to analyze the concept of audience, the concept of social systems, and the concept of the media system to find facts about the role of communication media and their effects on the development of tourist villages in Bali. After collecting data through literature study, this research succeeded in finding facts about two important things. First, the role of communication media for the development of tourist villages in Bali which is identified as a source and information center for tourist villages. In this case, the audience is assumed to be highly dependent on communication media, both print and digital media, as well as social media. The media serves as a source of information. There is a dependence of the audience on the media as a source of information. Messages that are needed by the audience such as tourist sites, physical infrastructure such as roads, electricity, water, hotels and restaurants, gift shops, banks, culinary tours. In addition, the media is important to inform about the existence of social infrastructure, climate/social situation such as an open and friendly society towards tourists, ease of business licensing in the tourism sector, environmental protection/preservation. Second, the effect of mass media on the development of tourist villages in Bali. The types of effects that can be identified and interpreted by the data include: (a) Cognitive effects, namely: creating clear messages or information about tourism products offered through mass media; (b) Affective effect, providing information to tourists about things that are taboo which if violated can experience unwanted things, an information that provides a deterrent effect to do things that are contrary to local cultural values. (c) Behavioral effects, namely: an agreement to work together to do positive things after experiencing something positive in places that have been visited.